A comparative study of characteristics in diploid and tetraploid Anoectochilus roxburghii - Huang, Xiaoling; Ouyang, Kunxi; Luo, Yongzhi; Xie, Guohong; Yang, Yuesheng; Zhang, Junjie (Frontiers in Nutrition, 2022)
Artificial induction of polyploidy is an efficient technique for improving biological properties and developing new varieties of many plants. In this study, we analyzed and compared differences in characteristics (morphological and biological) of diploid and tetraploid Anoectochilus roxburghii plants. We found significant differences between tetraploid plants and their diploid counterparts. The tetraploid plants exhibited dwarfing and stockiness. They were also bigger and had more voluminous roots and larger stomata than the diploid plants. Moreover, the biochemical analyses showed that the contents of some amino acids and minerals elements were significantly higher in tetraploid plants. The chlorophyll content of the leaves exhibited no definitive changes, but the photosynthetic performance was higher in the tetraploid plants. In addition, contents of major bioactive compounds, such as kinsenoside and some flavonoids, were enhanced in tetraploids. This is the first detailed analysis of characteristics in diploid and tetraploid A. roxburghii plants. The results may facilitate breeding programs with the species.